Gone with the Storm : Rainfall Shocks and Household Well-Being in Guatemala - Baez, Javier E.; Lucchetti, Leonardo; Genoni, Maria E.; Salazar, Mateo (World Bank Group, Washington, DC, 2015)
This paper investigates the causal consequences of Tropical Storm Agatha (2010) -- the strongest tropical storm ever to strike Guatemala since rainfall records have been kept -- on household welfare. The analysis reveals substantial negative effects, particularly among urban households. Per capita consumption fell by 12.6 percent, raising poverty by 5.5 percentage points (an increase of 18 percent). The negative effects of the shock span other areas of human welfare. Households cut back on food consumption (10 percent or 43 to 108 fewer calories per person per day) and reduced expenditures on basic durables. These effects are related to a drop in income per capita (10 percent), mostly among salaried workers. Adults coped with the shock by increasing their labor supply (on the intensive margin) and simultaneously relying on the labor supply of their children and withdrawing them from school. Impact heterogeneity is associated with the intensity of the shock, food price inflation, and the timing of Agatha with respect to the harvest cycle of the main crops. The results are robust to placebo treatments, household migration, issues of measurement error, and different samples. The negative effects of the storm partly explain the increase in poverty seen in urban Guatemala between 2006 and 2011, which national authorities and analysts previously attributed solely to the collateral effects of the global financial crisis.